Tele Alert System Based on ECG Signal Using Virtual Instruments Environment - Saif Al-din, Saif, M. N.; Mahmood, Sawsan. D; Abdulbaqi, Azmi Shawkat; Panessai, Ismail Yusuf; Yani, Achmad; Manaf, Abdi; Iksan, Nur (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This manuscript addresses the design and implementation of a portable PC-based ECG device. Three electrodes are often employed for ECG recording, with two of them being connected to the patient's chest via the ECG amplifiers' differential inputs. Therefore, every stage of the design takes into account factors like low cost, low power consumption, portability, and simplicity of usage. In this system, the ATMEL Company's ATMEGA 328 low-power microcontroller is investigated for signal processing and delivering digital format to a PC through a serial connection, where it is then displayed utilizing LabVIEWTM SP1 software ( The released version in Feb. 2022). A portable tool that can capture, amplify, filter, and analyze biological signals is this one ECG. The intended device's target beneficiary was the intensive care unit.